Mechanisms and Therapeutic Strategies of Viral Myocarditis Targeting Autophagy - Kun Yu; Ling Zhou; Yinhui Wang; Chengxin Yu; Ziyi Wang; Hao Liu; Haoran Wei; Liang Han; Jia Cheng; Feng Wang; Dao Wen Wang; Chunxia Zhao (Frontiers Media S.A., 2022)
Viral myocarditis is caused by infection with viruses or bacteria, including coxsackievirus B3 (CVB3), and is characterized by acute or chronic inflammatory responses in the heart. The mortality associated with severe viral myocarditis is considerable. In some patients, viral myocarditis may develop into dilated cardiomyopathy or heart failure. Autophagy is involved in a wide range of physiological processes, including viral infection and replication. In the present review, we focus on the responses of cardiac tissues, cardiomyocytes, and cardiac fibroblasts to CVB3 infection. Subsequently, the effects of altered autophagy on the development of viral myocarditis are discussed. Finally, this review also examined and assessed the use of several popular autophagy modulating drugs, such as metformin, resveratrol, rapamycin, wortmannin, and 3-methyladenine, as alternative treatment strategies for viral myocarditis.